Peran Orang Tua Balita Dalam Program Penurunan Stunting Di Wilayah Kerja Puskesmas Mandai Kabupaten Maros - Andi M. A Yandini; Nurmiati Muchlis; Nurbaeti (Window of Public Health Journal, 2025)
In the 2020 Ministry of Health work report data, the Target prevalence of stunting in toddlers in 2020 was 24.1% (5,543,000 toddlers). The ePPGBM SIGIZI report as of January 20, 2021, from 34 provinces explained that out of 11,499,041 toddlers with nutritional status according to height for age (TB/A), there were 1,325,298 toddlers with TB/A <-2 SD. It can be explained that 11.6% of toddlers experienced stunting. The type of research conducted is quantitative research. The research method used is cross-sectional using observation. Sampling in this study used a purposive sampling technique, using the Slovin formula because the initial data was known. The population was known to be 415, and the number of samples obtained was 204 respondents. The results of this study indicate that there is a relationship between Income, Education, Parenting Patterns, and Toddler Visits to Posyandu with Stunting Incidents, obtaining a p-value of 0.000 <0.05. Thus, it is recommended that parents of toddlers learn the correct parenting patterns, routinely take toddlers to posyandu and immunization, and find out about stunting.